2016
DOI: 10.1097/aud.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Mechanical Impedance of the Skin-Covered Skull: Implications for Soft Band Bone-Anchored Hearing Systems Fitted in Infants and Young Children

Abstract: Our findings show that mechanical impedance properties change systematically up to 7 years old. The significant age-related differences in mechanical impedance suggest that infant-adult differences in bone conduction thresholds may be related, at least in part, to properties of the immature skull and overlying skin and tissues. These results have important implications for fitting the soft band BAHS on infants and young children. For example, verification of output force form a BAHS on a coupler designed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…However, their impedances are around 5 dB lower overall at 1 kHz compared to the current results. The current results at the mastoid are within 2 dB from the impedances of the mastoid with 2 N static force of adults in Mackey et al (2016). Moreover, Mackey et al (2016) showed that the mastoid mechanical impedance with 5.4 N static force was 3 to 5 dB higher than with 2 N static force in adults.…”
Section: Mechanical Point Impedancementioning
confidence: 49%
See 1 more Smart Citation
“…However, their impedances are around 5 dB lower overall at 1 kHz compared to the current results. The current results at the mastoid are within 2 dB from the impedances of the mastoid with 2 N static force of adults in Mackey et al (2016). Moreover, Mackey et al (2016) showed that the mastoid mechanical impedance with 5.4 N static force was 3 to 5 dB higher than with 2 N static force in adults.…”
Section: Mechanical Point Impedancementioning
confidence: 49%
“…The current results at the mastoid are within 2 dB from the impedances of the mastoid with 2 N static force of adults in Mackey et al (2016). Moreover, Mackey et al (2016) showed that the mastoid mechanical impedance with 5.4 N static force was 3 to 5 dB higher than with 2 N static force in adults. Consequently, the slightly lower impedances for the mastoid reported here compared to Flottorp and Solberg (1976) and Håkansson et al (1986) is likely an effect of the lower static force used in the current study.…”
Section: Mechanical Point Impedancementioning
confidence: 67%
“…The output properties of BCDs are affected by the mechanical impedance of the load ( Weece and Allen, 2010 ). Several researchers have thoroughly investigated the impedance of the mastoid, and the results showed that the mastoid impedance was influenced by age ( Flottorp and Solberg, 1976 ; Zhang, 1994 ; Mackey et al, 2016 ; Nie et al, 2022 )), and that differences in mastoid impedance will lead to differences in the output force of the BC transducer. In addition, there are some differences in mastoid impedance between Chinese subjects and B&K 4930 artificial mastoid ( Nie et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The physical properties that may explain the different IAA across frequencies were elucidated in the fundamental study by Mackey et al (2016). The authors measured the magnitude of mechanical impedance to vibratile force transduced by a bone conduction hearing device placed on the mastoid or forehead of infants, children, and adults across frequencies of 100 to 10,000 Hz.…”
Section: Effect Of Frequencymentioning
confidence: 99%
“…The resonance frequency is characterized by the point of lowest impedance across the frequencies and a zero-phase delay. Mackey et al (2016) showed that infants had significantly lower impedance in the lower frequencies when compared with adults. In the higher frequencies, infants had higher impedance when compared with adults.…”
Section: Effect Of Frequencymentioning
confidence: 99%